Impacts and Challenges of Digital Technology on Cooperatives in Bali Province - RUSTARIYUNI, Surya Dewi; PUDJIHARDJO, M.; BURHAN, M. Umar; SATRIA, Dias (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).07, 2025)
This study aims to explore the impacts and challenges of cooperatives that use digital technology in the Province of Bali. The relevance of this work is the demand for digitalization of cooperatives by the central government to increase the empowerment of cooperative institutions and the lack of cooperatives that apply digital technology. A qualitative approach was used, and data analysis was conducted using the semantic interpretation method by conducting in-depth interviews using a purposive sample method with 47 cooperative top management who are using digital technology. The basis of this research methodology is organizational theory in the context of digitalization. The object of this work is cooperatives that apply digital technology. Digital cooperatives which are using organizational theory were the investigated objects showing the novelty of this work. It has been found that the impact of the use of digital technology by cooperatives influences increasing business prospects, business continuity, outreach and collaboration. However, it was found that cooperative members who are using mobile cooperatives have low loyalty. The risks faced are still challenging digital cooperatives, and it is recommended that further research be conducted to find out the reasons of cooperatives that have not implemented digital technology services.